The changeable political map of the Upper Adriatic region: from conflict to harmony - Bufon, Milan (Journal for Geography, 2008)
The paper will present a geopolitical and political geographical overview of the Upper Adriatic region as an area of contact between different cultural, social, economic and political entities, producing potential of conflicts, particularly in the period of growing nationalism and emerging nation-state formulation in this region.